2018
DOI: 10.3390/app8102000
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intermediate Principal Stress on Compressive Strength of Different Cement Content of Cement-Stabilized Macadam and Different Gradation of AC-13 Mixture

Abstract: Since the effect of intermediate principal stress on the strength of pavement materials is not entirely clear so far, a proprietary true triaxial apparatus was developed to simulate the spatial status of principal stresses to conduct compressive strength tests on different gradations of AC-13, different cement contents of cement-stabilized macadam. With the same minimum principal stress, the triaxial compressive strengths of cube specimens under different intermediate principal stresses were compared. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Mogi found that in true triaxial testing of many rock samples, the effect of the intermediate principal stress must be considered for rock [21]. The results of complex stress tests for concrete indicate that the intermediate principal stress also has a marked effect on the strength of concrete [27,28]. We can conclude that the intermediate principal stress effect is an inherent mechanical behavior of many materials.…”
Section: Introductionmentioning
confidence: 85%
“…Mogi found that in true triaxial testing of many rock samples, the effect of the intermediate principal stress must be considered for rock [21]. The results of complex stress tests for concrete indicate that the intermediate principal stress also has a marked effect on the strength of concrete [27,28]. We can conclude that the intermediate principal stress effect is an inherent mechanical behavior of many materials.…”
Section: Introductionmentioning
confidence: 85%
“…σ c is the uniaxial compressive strength, MPa. UST has been widely used in cement concrete, rock and soil materials (Kolupaev et al, 2013;Guan et al, 2018;Yu, 2018;Deng et al, 2020). Lijun et al (Suo et al, 2015) confirmed that the second principal stress, test temperature and loading rate have effects on the strength of asphalt mixture, but the exact influence law does not get.…”
Section: Unified Strength Theorymentioning
confidence: 99%
“…As the main road material, the mechanical properties of asphalt mixtures, especially direct tensile, uniaxial compression, and confining triaxial strength characteristics are quite important parameters for the design of mixture composition and the combined design of asphalt pavement structures [2]. Asphalt mixtures strength parameters are important parameters for pavement design [3].…”
Section: Introductionmentioning
confidence: 99%